A case report of hemolytic streptococcal gangrene in the danger triangle of the face with thrombocytopenia and hepatitis - Xiao-ling Jia; Janak L. Pathak; Jin-fa Tong; Ji-mei Su (BMC, 2018)
Abstract Background Hemolytic streptococcus gangrene is a life threatening invasive bacterial infection. Hemolytic streptococcus gangrene in the danger triangle of the face is too lethal to operate. A case of the confirmed hemolytic streptococcus gangrene in the danger triangle of the face caused by Group A beta-hemolytic streptococcus (GAS) in 20-months old boy is presented to draw attention of clinicians to this uncommon but frequently fatal infection. Case presentation Previously healthy 20 months old boy suddenly developed paranasal gangrene on the left side of the danger triangle of the face, followed by rapidly progressive thrombocytopenia and hepatitis. The clinical features, liver function, and hematological and serological parameters resembled to a description of streptococcal toxic shock syndrome (STSS). Aggressive antibiotics, substitutional and supportive therapy were conducted without surgical debridement of facial tissues. Prompt diagnosis and aggressive timely treatment completely cured the disease in 28 days. Conclusions The present case report demonstrates prompt diagnosis and timely treatment as a strategy to cure the fatal hemolytic streptococcus gangrene located in too risky body part to operate.